Designing and verifying an instrument to measure religiosity - Hasan Shahmirzalou; Hassan Rafiey; Mir Taher Mousavi; Gholamreza Ghaedamini Harouni; Zahra Hosseini Safa (Shahid Beheshti University of Medical Sciences, 2019)
For downloading the full-text of this article please click here. Background and Objective: In spite of the paramount importance of religion in human life, the definition of its domain, concepts, and components is subject to theoretical and methodological uncertainty. The root of many of these ambiguities lies in the absence of appropriate measurement tools. Given that, the main purpose of this research is validating and determining reliability of a local instrument for measuring religiosity. Method: This study aimed at developing an instrument. The participants were provided with researchers' questionnaire developed after studying documents and providing the theoretical framework, preparing question banks and validity. The sample, 500 adult citizens over 18 years old in 22 districts of Tehran selected by using random sampling and classification according to gender, age, and area of residence. The obtained data were utilized for exploratory factor analysis, Cronbach's alpha reliability, validity criteria, indicators fitted, and eventually the introduction of religiosity questionnaire. In this research, all the Ethical issues were observed and authors declared no conflicts of interest. Results: Based on exploratory factor analysis (EFA), seven factors accounted for 65.67% of the religiosity variance. The results of exploratory factor analysis (RMSEA=0.08, CFI=0.907, GFI=0.869) show the 21-item questionnaire has an acceptable fit. The internal consistency (α=0.83) and consistency over time also indicated that the final questionnaire has acceptable reliability. Conclusion: Results show that the developed questionnaire is acceptable in terms of validity and reliability to be used in Islamic societies for measuring religiosity. For downloading the full-text of this article please click here. Please cite this article as: Shahmirzalou H, Rafiey H, Mousavi MT, Ghaedamini Harouni Gh, Hosseini Safa Z. Designing and verifying an instrument to measure religiosity. J Res Relig Health. 2019; 5(2):6- 22. doi: https://doi.org/10.22037/jrrh.v5i2.19300.